The Urgency of Implementing Restorative Justice in Handling Juvenile Crime: A Study of The Principles of Humanity And Justice - Flora, Henny Saida (PT. Anagata Sembagi Education, 2025)
This article examines the urgency of implementing restorative justice in handling juvenile crime by analysing the principles of humanity and justice that should guide child-centered legal processes. Using a normative juridical method combined with conceptual and comparative analysis, the study demonstrates that punitive criminal justice responses are incompatible with the developmental characteristics and human dignity of children. Restorative justice offers a more appropriate framework by emphasizing harm repair, accountability, dialogue, and reintegration. The findings reveal significant structural barriers to implementation in Indonesia, including limited facilitator capacity, inadequate victim support, fragmented inter-agency coordination, socio-economic disparities, and persistent punitive cultural attitudes. The article argues that meaningful restorative justice requires clear legal guidelines, standardized procedures, institutional training, community engagement, and integrated social support services addressing the root causes of juvenile offending. Strengthening restorative justice is imperative to ensure that children in conflict with the law are treated with dignity, fairness, and proportionality. The study offers policy recommendations to embed restorative principles in national justice systems, making juvenile handling more humane, equitable, and effective